Legal Analysis of Interfaith Marriage in Indonesia: Challenges and Comparison with Turkish Marriage Law - Felicia Ivana (Faculty of Law, Universitas Pekalongan, 2024)
Interfaith marriage has become a topic ofinterest in social and cultural studies, especiallyin countries with significant religious diversity.This article aims to investigate the dynamics ofinterfaith marriage law in Indonesia, includingthe challenges faced and future prospects. Inaddition, this article will also compare thepractice of interfaith marriage law in Indonesiawith the legal practice in Turkey, as a countrywith a similar background in the context of amulticultural society and a majority Muslimpopulation. This study uses a doctrinalresearch method with a comparative approach.The researcher also uses document studies orlibrary materials such as legal journals, books,and Legislation, namely Law Number 1 of 1974concerning Marriage, Constitutional CourtDecision Number 24/PUU-XX/2022 andSupreme Court Circular Letter No. 2 of 2023concerning Guidelines for Judges inAdjudicating Cases of Applications forRegistration of Marriages Between People ofDifferent Religions and Beliefs, The TurkishFamily Law of Cyprus of 1951 and TurkishCivil Code No. 4721. This study shows that theDecision of the Constitutional Court Number24/PUU-XX/2022 and the Circular of theSupreme Court No. 2 of 2023 concerningGuidelines for Judges in Adjudicating Cases ofApplications for Registration of MarriagesBetween People of Different Religions andBeliefs prohibit the implementation ofinterfaith marriages absolutely and ignorereligious interpretations that allow interfaithmarriages and only refer to the majorityreligious interpretation. Indonesia and Turkey present interesting legal arrangements andhave significant differences in the context ofmarriage and interfaith marriages. Accordingto Turkish Marriage Law, religion and beliefare not obstacles to the implementation of amarriage. With a deeper understanding of thecomparison between Indonesia and Turkey, itis hoped that it can provide new insightsregarding more inclusive and comprehensivepolicies regarding interfaith marriages inIndonesia